1995
DOI: 10.4319/lo.1995.40.2.0273
|View full text |Cite
|
Sign up to set email alerts
|

The biofilm polysaccharide matrix: A buffer against changing organic substrate supply?

Abstract: In contrast to the widely held view that microorganisms respond rapidly to changes in environmental conditions, the microbes in biofilms appear remarkably resilient to substantial changes in the abundance of dissolved organic substrates. Removal of high-molecular-weight dissolved materials from waters supplied to river biofilms generally did not affect bacterial densities or the synthesis of phospholipids and DNA. Even the complete elimination of exogenous materials from the overlying waters allowed heterotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(85 citation statements)
references
References 26 publications
7
76
0
2
Order By: Relevance
“…In streams, biofilms adsorb, retain, amplify and transform organic substances and nutrients in the matrix 100,101 (see the figure, part c), thereby accumulating substances that are otherwise highly diluted in the streamwater, such as dissolved organic carbon or contaminants. These solutes become concentrated in biofilms via adsorption to the matrix or incorporation into microbial biomass and subsequent release to the extracellular space 100,101 .…”
Section: Several Crucial Questions Relating To the Biology Of Stream mentioning
confidence: 99%
See 1 more Smart Citation
“…In streams, biofilms adsorb, retain, amplify and transform organic substances and nutrients in the matrix 100,101 (see the figure, part c), thereby accumulating substances that are otherwise highly diluted in the streamwater, such as dissolved organic carbon or contaminants. These solutes become concentrated in biofilms via adsorption to the matrix or incorporation into microbial biomass and subsequent release to the extracellular space 100,101 .…”
Section: Several Crucial Questions Relating To the Biology Of Stream mentioning
confidence: 99%
“…These solutes become concentrated in biofilms via adsorption to the matrix or incorporation into microbial biomass and subsequent release to the extracellular space 100,101 . Biofilms have reflective characteristics similar to those provided by an ecological boundary; the resident microbiome may sort and reflect invading microorganisms 102 with consequences for local community assembly and downstream release of microorganisms.…”
Section: Several Crucial Questions Relating To the Biology Of Stream mentioning
confidence: 99%
“…The polyanionic polysaccharide matrix in the biofilm can capture OC and other nutrients from the stream water by ion exchange. Microbes use these resources as energy sources (Freeman and Lock 1995;Storey et al 1999). Denitrification rates can be higher in biofilms than in other sites such as stream water due to the supply of a highly-degradable OC and nutrients from biofilms (Howard-Williams et al 1989;Christensen et al 1990;Mariñelarena and Giorgi 2001;Bastviken et al 2003;Toet et al 2003;Venterink et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ecosystem service (Paterson et al 2008) of particle capture and retention is of great importance to sediment systems in balancing the replacement of material lost by tidal erosion (Verney et al 2006) or wave action (Andersen et al 2007), enhancing the nutrient status (Freeman and Lock 1995) and offering binding sites for pollutants (Ghosh et al 2003). This biofilm adhesion can be measured with high sensitivity, and small changes in developing biofilms can be demonstrated that would be unnoticed using established erosion devices.…”
Section: Comments and Recommendationsmentioning
confidence: 99%